2016
DOI: 10.1515/hukin-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Enlargement in Young High-Level Endurance Athletes – Another Sign of Athlete’s Heart?

Abstract: Enlargement of the left atrium is perceived as a part of athlete’s heart syndrome, despite the lack of evidence. So far, left atrial size has not been assessed in the context of exercise capacity. The hypothesis of the present study was that LA enlargement in athletes was physiological and fitness-related condition. In addition, we tried to assess the feasibility and normal values of left atrial strain parameters and their relationship with other signs of athlete’s heart. The study group consisted of 114 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…The atrial enlargement, which is dynamic and reversible, is an adaptive mechanism in response to the increased training-induced volume overload, and it may vary by sex. In a study consisting of young elite rowers (46.5% women), LA enlargement was found more frequently in men than in women [75]. Similar to the LA, greater right atrium (RA) dimensions were observed in elite athletes compared to sedentary control subjects [76].…”
Section: Combinedmentioning
confidence: 98%
“…The atrial enlargement, which is dynamic and reversible, is an adaptive mechanism in response to the increased training-induced volume overload, and it may vary by sex. In a study consisting of young elite rowers (46.5% women), LA enlargement was found more frequently in men than in women [75]. Similar to the LA, greater right atrium (RA) dimensions were observed in elite athletes compared to sedentary control subjects [76].…”
Section: Combinedmentioning
confidence: 98%
“…Regular and intense physical activity leads to several morphological and functional adaptive heart modifications that have been known as "athlete's heart" (Król et al 2016). The extent of these physiological cardiovascular "adaptive" changes is predominantly related to the intensity and type of sport activity and highly depends on the type of physical training (Santoro et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even in athletes with advanced atrial remodelling, the left atrial function remains normal, similarly to the left ventricle. Moreover, it has been shown that left atrial volume correlated with exercise capacity in professional athletes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%